If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 109 + -3x = 24x + 19 Reorder the terms: 109 + -3x = 19 + 24x Solving 109 + -3x = 19 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 109 + -3x + -24x = 19 + 24x + -24x Combine like terms: -3x + -24x = -27x 109 + -27x = 19 + 24x + -24x Combine like terms: 24x + -24x = 0 109 + -27x = 19 + 0 109 + -27x = 19 Add '-109' to each side of the equation. 109 + -109 + -27x = 19 + -109 Combine like terms: 109 + -109 = 0 0 + -27x = 19 + -109 -27x = 19 + -109 Combine like terms: 19 + -109 = -90 -27x = -90 Divide each side by '-27'. x = 3.333333333 Simplifying x = 3.333333333
| 1-2x=5+3x | | 11x+7=5x+61 | | (5x/4)=13 | | 8x+7=-2 | | 10y=4x-4 | | 5x+8=-4+3x | | a/7+6=12 | | x+8=-4+3x | | 7a+7=63 | | 4x+12=14-9x | | 5x+8=4+3x | | (16x^2+20x-6)/(2x^2-9x-56) | | (5x+2)(2x^2-9x-5)=0 | | 2(y-4)=-4y-10 | | x+3(x+3)=10 | | (100/4)^-1/2 | | 7-4x=-6x+1 | | 6=x+1/x | | -7x^2+24-9=0 | | 4x/2x | | 8(x-9)=7 | | 2x+6x=12 | | 2c+6c+8+=32 | | 3(2+1)=8 | | (4x-1)/(2x^2-3) | | -2x+6=-x+5 | | =11m-3n-3s | | 2x^2-8+3=0 | | 12x-1+2x=x+1 | | -12+27x=-12 | | 10x+10x=118+x | | -3x^2-8x+35=0 |